Financing Principles in Islamic Banking - Sharifova Fayyoza Bekmurod qizi (International Journal on Economics, Finance and Sustainable Development, 2022)
The article notes that Islamic banking is the main developing part of banking sector around the globe. Nowadays, the number of banks working in Islamic principles is rising and their benefit also is higher than the traditional ones according to some statistics. Interest (Riba) is confirmed as haram by Sharia, so they possess sharia-compliant activities. This article reveals the essence of the category of “islamic financing”, shows the ways how to finance the corporate clients and individuals, analyses the procedure and advantages of using Islamic principles than credits in banking sector. And what deserves attention is that the article formulates a number of characteristics, on the basis of which the author’s own version of the definition of the category “Islamic financing” has been developed.